Comparison of 10‐year Outcomes of Bryan Cervical Disc Arthroplasty for Myelopathy and Radiculopathy. Issue 6 (25th November 2019) - Han, Xiao; He, Da; Zhang, Ning; Song, Qingpeng; Wang, Jinchao; Tian, Wei
Abstract : Objective: To evaluate the long‐term efficacy of Bryan cervical disc arthroplasty in the treatment of myelopathy patients compared with radiculopathy patients. Methods: This study is a prospective study. Sixty‐six patients (38 patients in myelopathy group and 28 patients in radiculopathy group) who were treated with Bryan cervical disc arthroplasty between 2004 and 2007 and followed for 10 years were included in this study. The Japanese Orthopaedic Association (JOA) score, neck disability index (NDI), and Odom's criteria were used to evaluate the clinical outcomes. X‐ray, computed tomography (CT), and magnetic resonance imaging (MRI) were used to evaluate the radiographic outcomes including the global range of motion (ROM), segmental ROM, and segment alignment before the surgery and at last follow‐up. The incidence of segmental kyphosis, segmental mobility lost, and the grade of paravertebral ossification (PO) were also evaluated at last follow‐up. Results: The JOA score and NDI improved in both groups. Thirty‐three of 38 patients in myelopathy group and all patients in radiculopathy group reported good or excellent outcomes according to Odom's criteria. The segmental ROM was (9.5° ± 4.4°) before surgery and maintained at (9.0° ± 5.5°) at last follow‐up in myelopathy group. The segmental ROM was (9.5° ± 4.6°) and (9.0° ± 5.3°) before surgery and at last follow‐up in radiculopathy group, respectively. The Bryan prosthesis remained mobile at last follow‐up for 30 patients (78.9%) in the myelopathy group and 22 patients (78.6%) in the radiculopathy group. Of the patients in the myelopathy group, 21.1% developed segmental kyphosis, as did 21.4% of patients in the radiculopathy group. The incidence of PO and high‐grade PO was 92.1 and 28.9% in the myelopathy group, and was 92.9 and 32.1% in the radiculopathy group. There was no significant difference between both groups. Conclusions: Bryan cervical disc arthroplasty was an effective and safe technique in treating patients with myelopathy. The clinical and radiographic outcomes in the myelopathy group were similar to those in the radiculopathy group at the 10‐year follow‐up.